Analisis Penilaian dan Evaluasi Capaian Hasil Belajar Matematika pada Materi Bangun Ruang dalam Implementasi Kurikulum Merdeka di SMA N 1 Girsang Sipangan Bolon - Situmorang, Purnama Raya Anjelina; Togatorop, Fresty Handayani; Panggabean, Ellis Mardiana; Situmorang, Adi Suarman (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe the implementation of assessment and evaluation of mathematics learning outcomes in spatial geometry material in the Merdeka Curriculum at SMA Negeri 1 Girsang Sipangan Bolon. The study used a descriptive qualitative approach with data collection through observation, interviews, and document analysis. The results of the study indicate that teachers have implemented formative assessment, practical assessment, and context-based assignments. However, authentic assessment has not been implemented consistently, and assessment instruments still tend to focus on students' procedural abilities, so that contextual abilities have not been optimally explored. The main obstacles in the implementation of assessment include limited learning time, the administrative burden on teachers, and teachers' skills in developing and using assessment rubrics. This study concludes that the implementation of assessment on spatial geometry material has been in line with the principles of the Merdeka Curriculum, but it still requires improvement in teacher competence and institutional support from the school so that assessment can be carried out more optimally.